ANALYSING THE USE OF GROWTH RATIOS AND CONCEPTS AS TOOLS TO DETERMINE THE FOCUS OF TAX AUDITS - Fitriana Fitriana; Alexandre de Sousa Guterres; M. Syahrudin; Vip Paramarta; Kosasih (CV. Adiba Aisha Amira, 2024)
This study aims to explore the use of financial ratios and growth concepts as tools in determining the focus of tax audits. The research method used in this study is the literature method. The results of this study offer valuable insights for tax authorities in developing a more targeted and efficient audit strategy. This study also provides an analytical framework for tax authorities in developing a more data-driven audit approach, which can ultimately improve the fairness and integrity of the tax system. As such, this study makes a significant contribution to the tax auditing literature and audit practice, and supports efforts in improving tax compliance through innovation and utilisation of analytical tools.